2018
DOI: 10.1002/cnr2.1130
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of FGFR3 gene mutation and its correlation with clinicopathological findings in Indian bladder cancer patients

Abstract: Background: Molecular alteration of FGFR3 gene is the most common genetic event currently known in bladder cancer. Notably, FGFR3 mutation has emerged as a promising molecular biomarker for recurrence, prognosis, and therapeutic target in bladder cancer. Aim:The present study explored the frequency and distribution pattern of FGFR3 mutation in 100 Indian bladder cancer patients.Methods and results: Exons 7, 10, and 15 were subjected to nested PCR followed by bidirectional sequencing of the PCR products. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…The role of FGFR3 in predicting the prognosis and progression remains unclear. Mutation studies done on two groups of the same have reported an association between mutations and a higher recurrence rate (Mhawech-Fauceglia P et al, Van Oers et al) (21,22, 23) , whereas others are contrary (van Rhijn BW et al, Hernández S et al) (24,25). Few studies have been done by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 98%
“…The role of FGFR3 in predicting the prognosis and progression remains unclear. Mutation studies done on two groups of the same have reported an association between mutations and a higher recurrence rate (Mhawech-Fauceglia P et al, Van Oers et al) (21,22, 23) , whereas others are contrary (van Rhijn BW et al, Hernández S et al) (24,25). Few studies have been done by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 98%
“…FGFR3 was a carcinogenic driver, and the mutation, activation, and overexpression of FGFR3 are common in bladder cancer ( Guancial et al, 2014 ; Pouessel et al, 2016 ). Ahmad once explored the frequency of FGFR3 mutation in Indian bladder cancer patients and found that FGFR3 mutations were more common in the low pathological stage and low-grade tumors ( Ahmad et al, 2018 ). Taken together, the effect caused by mutation of TP53 , RB1 , MUC16 , and FGFR3 were in accord with risks predicted by hypoxia risk scores in our study.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR3 was a carcinogenic driver and the mutation, activation, and overexpression of FGFR3 was common in BC [ 53 , 54 ]. Ahmad once explored the frequency of FGFR3 mutation in Indian BC patients and found that FGFR3 mutations were more common in earlier pathological stage and low-grade tumors [ 55 ]. TP53 and RB1 played a role of suppressor genes in all cancer, which encoded p53 and rb1 protein involved in regulating numerous target genes.…”
Section: Discussionmentioning
confidence: 99%